Gambaran Tingkat Depresi Lansia di Panti Sosial Lanjut Usia Tulungagung - Tragara Zalzal Sciora (Jurnal Ners dan Kebidanan, 2015)
The process of aging is a process of gradual disappearance of the network’s ability to improve. Depression is one of the most common disorders in the elderly who need handling holistic and balanced in the physical, mental and social. The research aim was to indentify the grade of depression elderly people in Blitar society service of elderly people at Tulungagung. The research design used descriptive research. The population of this research was all of elderly at Blitar society service of elderly people at Tulungagung. The sampel size was 45 elderly (21 men elderly and 24 women elderly) with porposive sampling. The research held on 21 febuary 2014 at Blitar society service of elderly people at Tulungagung. In this research, data was preserved in descriptive analysis with fequency table and radian diagram by percentage and narration. From the research result got the elderly had no depression amount 17,8%, the next elderly with light depression amount 22,2%, the next elderly with medium depression amount 22,2% and elderly with heavy depression amount 37,8%. From the results of researches are expected to managers elderly people in Blitar society service of elderly people at Tulungagung. improve services for the prevention of cases of depression in the elderly.